Tracing the Print Culture of Female Travel Writers and the Influence of Gender and Race on their Perception and Publication - GOUAICH, Leila (My University, 2020)
This dissertation traces the print culture of female writers since the turn of the twenty-first century and the influence of gender and race on their perception and publication. In a society that is bound by social sanction, gender identity is performative and thus self perpetuated by those who adhere to their prescribed roles for fear of marginalization. This study aims to investigate the extent to which the ideologically gendered genre of travel writing continues to inflect current publishing practice. A case study of two successful female travelogues are carried out to investigate whether British publishing houses are attempting to amend existing practice in light of the genre’s entrenched inequalities. The rise of digital platforms and the travel blogosphere since the turn of the century have assisted in the diversification of travel writing. Yet the fact that minority voices both online and in print rarely receive the exposure required to infiltrate mainstream awareness evidences that it falls to both readers and the wider publishing industry to break the systemic diversity issues which are endemic in the travel writing genre.
Keywords: Gender; Race; Travel writing; Digital platforms; Publishing houses